Analysis of the Role of Labor Law in Improving the Regeneration and Welfare of Farmers to Welcome to the World's World's Rice Bans - Paiza Aprilia Saputri; Angga Maghrifin Suryanto; Viernanda Prahma Radhyvkha; Fitra Mutiara Al Hasna; Annisa Kartika Putri; Mirza Muhammad Fauzi; Vanka Iyandova (Proceeding International Conference Restructuring and Transforming Law, 2022)
The welfare of workers and farmers is one of the important factors that need to be considered by the Indonesian government, the level of welfare of workers in Indonesia is still quite low because it is still found to share problems in most areas, including: unskilled labor , lack of work space, low wages. low, and education factor. This study aims to analyze various kinds of problems that can affect the level of welfare of workers and farmers in Indonesia. This study also analyzes several solutions that have been carried out and that should be carried out by the government and the community to respond to the problems that cause the low level of welfare of workers and farmers in Indonesia.